DIPG in Children – What Can We Learn from the Past? - Vanan, Magimairajan Issai; Eisenstat, David D. (Frontiers in Oncology, 2015)
Brainstem tumors represent 10-15% of pediatric central nervous system tumors and diffuse intrinsic pontine glioma (DIPG) is the most common brainstem tumor of childhood. DIPG is almost uniformly fatal and is the leading cause of brain tumor-related death in children. To date, radiation therapy (RT) is the only form of treatment that offers a transient benefit in DIPG. Chemotherapeutic strategies including multi-agent neoadjuvant chemotherapy, concurrent chemotherapy with RT, and adjuvant chemotherapy have not provided any survival advantage. To overcome the restrictive ability of the intact blood brain barrier (BBB) in DIPG, several alternative drug delivery strategies have been proposed but have met with minimal success. Targeted therapies either alone or in combination with RT have also not improved survival. Five decades of unsuccessful therapies coupled with recent advances in the genetics and biology of DIPG have taught us several important lessons: (1) DIPG is a heterogeneous group of tumors that are biologically distinct from other pediatric and adult high grade gliomas (HGG). Adapting chemotherapy and targeted therapies that are used in pediatric or adult HGG for the treatment of DIPG should be abandoned. (2) Biopsy of DIPG is relatively safe and informative and should be considered in the context of multicenter clinical trials. (3) DIPG probably represents a whole brain disease so regular neuraxis imaging is important at diagnosis and during therapy. (4) BBB permeability is of major concern in DIPG and overcoming this barrier may ensure that drugs reach the tumor. (5) Recent development of DIPG tumor models should help us accurately identify and validate therapeutic targets and small molecule inhibitors in the treatment of this deadly tumor.